2021
DOI: 10.3390/antibiotics10091056
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use during the COVID-19 Pandemic in a Tertiary Hospital with an Ongoing Antibiotic Stewardship Program

Abstract: During the recent pandemic, the fact that the clinical manifestation of COVID-19 may be indistinguishable from bacterial infection, as well as concerns of bacterial co-infection, have been associated with an increased use of antibiotics. The objective of this study was to assess the effect of targeted antibiotic stewardship programs (ASP) on the use of antibiotics in designated COVID-19 departments and to compare it to the antibiotic use in the equivalent departments in the same periods of 2018 and 2019. Antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
1
13
1
2
Order By: Relevance
“…For example, antibiotic consumption was highest during the first wave, probably due to the uncertainty of how to treat COVID-19 patients [ 9 ], followed by a decline with the introduction of more specific treatment guidelines. This was also found in a study from Israel, where a continuous decrease in antibiotic consumption from wave to wave was observed [ 27 ]. However, especially for the sales data, an amplification of this effect by buying antibiotics in stock at the beginning of the pandemic cannot be ruled out.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…For example, antibiotic consumption was highest during the first wave, probably due to the uncertainty of how to treat COVID-19 patients [ 9 ], followed by a decline with the introduction of more specific treatment guidelines. This was also found in a study from Israel, where a continuous decrease in antibiotic consumption from wave to wave was observed [ 27 ]. However, especially for the sales data, an amplification of this effect by buying antibiotics in stock at the beginning of the pandemic cannot be ruled out.…”
Section: Discussionsupporting
confidence: 79%
“…At the beginning of the pandemic, due to the high occupancy rate of ICUs and general uncertainty about the treatment of COVID-19 patients, treating physicians may have tended to prescribe broad-spectrum antibiotics leading to increased prescribing of these antibiotics. As the pandemic progressed and the treatment of COVID-19 patients became more routine, this initially high consumption was adjusted—an aspect that is also supported by a study by Henig et al [ 27 ].…”
Section: Discussionmentioning
confidence: 72%
“…For example, in Israel, Henig et al described how they shifted the stewardship focus to the COVID-19 departments. In that setting, an intense stewardship program resulted in reduced antibiotic consumption through implementing new local guidelines and providing daily input from infectious disease consultants [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first case of coronavirus disease 2019 (COVID- 19) in Canada was identified on January 23, 2020, in Toronto, Canada. 1 From that point forward, COVID-19 cases waxed and waned throughout the city, which is Canada's largest city by population and one of the country's epicenters during the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…[12][13][14][15] Although some published data are available from the inpatient setting (generally demonstrating increased rates of antimicrobial prescribing during the first wave of the COVID-19 pandemic), most of these studies have only described early pandemic prescribing, and antibiotic use metrics were not always standardized to patient volumes or compared to baseline prescribing patterns. [16][17][18][19] Published data on the impact of the pandemic on ASPs, and how changes in ASPs may have affected antimicrobial consumption trends, are also limited. One study, which demonstrated a decrease in antimicrobial prescribing in COVID-19 units compared to historical controls, hypothesized that the ASP was responsible for the decreased rates of antimicrobial use.…”
mentioning
confidence: 99%